Os conteúdos e a prática pedagógica dos professores de educação física: análise do currículo do estado de São Paulo - Barros, André Minuzzo de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Contents organization and its role in the curriculum are recent and polemical subjects in the elementary school and high school physical education and it has been an usual discussion, notably from nowadays curriculum proposals presented by states of federation as São Paulo, Rio Grande do Sul, Minas Gerais, Santa Catarina, among others. The objective of this research was to describe and analyze how teachers interpret, evaluate and implement the contents provided in the Teacher‟s Handout. The methodological approach was of qualitative nature and the data collection involved the review of documents that support the Curriculum of São Paulo Teacher‟s Handout, Physical Education and field research, by means of semi-structured interviews and observation of teacher‟s classes. The interviews were done with seven Physical Education teachers teaching in at least one class of elementary school (cycle II) or high school of the SEE-SP public system, in the city of São Paulo, they declare that they know the contents provided in the Teacher‟s Handout and formally agreed to participate in the research. Two of them had been observed in their pedagogical practice. The data were discussed based on contents analysis. The results show that usually teachers ignore the conception of teaching and the inherent content concepts provided in the Teacher‟s Handout, recognizing better the amplification then its deepening. Teachers are favorable to the contents organization provided in the Teacher‟s Handout, but evaluate them in quite different measures, depending on mainly how they understand the teaching conception and its inherent concept. Teachers who implemented contents more coherently in relationship with the Curriculum of São Paulo proposals were the ones who had shown better capacity of interpret and evaluate the Teacher‟s Handout contents. Highlighting the knowledge of teaching conception as a fundamental element to the proper development of...

A organização dos conteúdos e o seu papel nos currículos são temas recentes e polêmicos na Educação Física escolar e têm aparecido frequentemente nas discussões e estudos da área, especialmente a partir da publicação das propostas curriculares apresentadas por diversos Estados da Federação, como São Paulo, Rio Grande do Sul, Minas Gerais, Rio de Janeiro, entre outros. Este estudo objetivou analisar como os professores de Educação Física do Ensino Fundamental - ciclo II e Ensino Médio, interpretam, avaliam e implementam os conteúdos apresentados nos Cadernos do Professor do Currículo do Estado de São Paulo. A abordagem metodológica foi de natureza qualitativa e a coleta dos dados envolveu a análise dos documentos que sustentam os Cadernos do Professor do Currículo de São Paulo na disciplina de Educação Física, e pesquisa de campo, por meio de entrevistas semiestruturadas e observações de aulas dos professores. As entrevistas foram realizadas com sete professores de Educação Física lecionando ao menos em uma turma do Ensino Fundamental (ciclo II) ou Ensino Médio, na rede pública da SEE-SP, na cidade de São Paulo, que declararam conhecer os conteúdos apresentados nos Cadernos do Professor e aceitaram participar da pesquisa. Dois desses professores foram observados em sua prática pedagógica. Os dados foram discutidos com base na análise de conteúdos. Os resultados apontaram que geralmente os professores desconhecem a concepção de ensino e os conceitos inerentes aos conteúdos apresentados nos Cadernos do Professor, reconhecendo melhor a ampliação que o aprofundamento destes. Os professores são favoráveis à organização dos conteúdos apresentada nos Cadernos do Professor, mas os avaliam em medidas bastante diferentes, dependendo principalmente de como compreendem a concepção de ensino e os conceitos inerentes a ele. Os professores que implementam os conteúdos de forma mais coerente com os...
Keywords: Physical education and training - Study and teaching; Educação física - Estudo e ensino; Educação fisica - Currículos; Professores - Formação; Inovações educacionais; Pratica de ensino; São Paulo (Estado)